Harrow the Ninth - Muir, Tamsyn (Muir, Tamsyn. Locked tomb trilogy, 2020)
"She answered the Emperor's call. She arrived with her arts, her wits, and her only friend. In victory, her world has turned to ash. Nothing is as it seems in the halls of the Emperor, and the fate of the galaxy rests on one woman's shoulders. Harrowhark Nonagesimus, last necromancer of the Ninth House, has been drafted by her Emperor to fight an unwinnable war. Side-by-side with a detested rival, Harrow must perfect her skills and become an angel of undeath -- but her health is failing, her sword makes her nauseous, and even her mind is threatening to betray her. Sealed in the gothic gloom of the Emperor's Mithraeum with three unfriendly teachers, hunted by the mad ghost of a murdered planet, Harrow must confront two unwelcome questions: is somebody trying to kill her? And if they succeeded, would the universe be better off?" --